Estudio de factibilidad para la creación de una empresa comercializadora de muebles para el hogar hechos a la medida en la comuna del café Pereira - Risaralda (2012)
The present project presents the different aspects to consider in order to determine the feasibility of the creation of a commercialization of wooden furniture made to the measured in the city of Pereira in the sector of the commune Café. This commune is separated by the river Otún is about 15 or 20 minutes from the center of the city ​​which gives an air of town to this locality. Furniture with heat of home is a company that will be dedicated to the commercialization of furniture with the great competitive advantage of making them to the spaces that provide the current homes and as the client wishes, accounts in Unique yet adjustable models that are today this form the project is inserted in the current market and at the same time it is returned to a proposal novelty worthy to be exported and to insert in the markets not only national but international, becoming an avant-garde idea. Thus, the idea of ​​this work, which aims at the development of a study feasibility study, which provides sufficient evidence to ensure the success of a project in this category, where many of the the course of the race. In this case the use of related studies with research markets, technicians, agencies, environmental and economic-financial, that contributed significantly in the construction of this business proposal that was within the present work, which has been perfected through the different knowledge acquired until reaching the final product that is presented today.